PENGARUH EXPERIENTAL MARKETING TERHADAP MINAT BELI ULANG PELANGGAN PADA RUMAH MAKAN BERINGIN INDAH PEMATANG SIANTAR - Amelia, Wan Rizca (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2017)
In the now era, there are various kinds of businesses. Especially the culinary business like a restaurant. The restaurant business in Siantar becomes is increasing and very competitive. Therefore, product does not become the priority for a company but consumers.. The objective of the research was to find out and analyze the influence of experiential marketing which consisted of sense, feel, think, act, and relate toward repurchase intention. The research used descriptive quantitative with explanatory research method. The population was the customers of Rumah Makan Beringin Indah which had visited it at least twice in the last 2 months. The samples were taken by using purposive sampling technique. The data were gathered by conducting interviews, questionnaires, and documentary study and analyzed by using multiple linear regression analysis. The results of the research showed that experiential marketing which consisted of sense, feel,think, act, and relate had a significant influence on the repurchase intention at Rumah Makan Beringin Indah. Â Â Keywords: Experiential Marketing, Repurchase Intention.